Blended Learning Outcomes in Academic and Professional Writing - Owens, Catherine (Journal of Education and Vocational Research, 2015)
Much has been written about the potential of online learning. Advantages discussed in the literature include practical considerations such as career preparation, convenience, and savings in time and money, the ethical benefit of open access and the environmental one of reduced paper and printing; learning benefits such as improved creativity and support for a more learner centered environment, learner autonomy, and the establishment of standards. This study documents the learning outcomes of 28 undergraduate students studying Professional and Academic Writing in a blended learning environment. Outcomes reflect gains in academic English writing skills, with specific reference to the use of the process approach to writing. Evidence from studentsâ€™e-portfolios provides a rich source of learners’ engagement in the planning, drafting, revising and presenting steps of paper completion. Further evidence shows how students develop information literacy through the use of the online learning materials. The instructional design features of particular tasks along with the e-portfolio used for formative evaluation are also analyzed for their contributions to the learning outcomes.